Antimicrobial Medicines Consumption in Eastern Europeand Central Asia – An Updated Cross-National Study and Assessment of QuantitativeMetrics for Policy Action - Robertson, Jane; Iwamoto, Kotoji; Hoxha, Iris; Ghazaryan, Lilit; Abilova, Vafa; Cvijanovic, Ana; Pyshnik, Halina; Darakhvelidze, Marina; Makalkina, Larissa; Jakupi, Arianit; Dzhakubekova, Aigul; Carp, Angela; et al. (Frontiers in Pharmacology, 2019)
Introduction Surveillance of antimicrobial medicines consumption is central to improving their use and reducing resistance rates. There are few published data on antibiotic consumption in Eastern Europe and Central Asia. To address this, 18 non-European Union (EU) countries and territories contribute to the WHO Regional Office for Europe (WHO Europe) Antimicrobial Medicines Consumption (AMC) Network. Objectives (i) Analyse 2015 consumption of J01 class antibacterials for systemic use from 16 AMC Network members; (ii) compare results with 2011 data and 2015 ESAC-Net estimates; (iii) assess consumption against suggested indicators; (iv) evaluate the impact of planned changes to DDDs in 2019 for some commonly used antibiotics; (v) consider the utility of quantitative metrics of consumption for policy action. Methods Analysis methods are similar to ESAC-Net for EU countries. The Anatomical Therapeutic Chemical (ATC) classification and defined daily doses (DDD) methodology were used to calculate total consumption (DDD/1000 inhabitants/day [DID]), relative use measures (percentages), extent of use of WHO Watch and Reserve group antibiotics and impact of DDD changes. Findings Total J01 consumption in 2015 ranged 8·0-41·5 DID (mean 21·2 DID), generally lower than in 2011 (6·4–42·3 DID, mean 23·6 DID). Beta-lactam penicillins, cephalosporins and quinolones represented 16·2 to 56·6%, 9·4 to 28·8%, and 7·5 to 24·6% of total J01 consumption respectively. Third-generation cephalosporins comprised up to 90% of total cephalosporin consumption in some countries. Consumption of WHO Reserve antibiotics was very low; Watch antibiotics comprised 17·3 to 49·5% of total consumption (mean 30·9%). Variability was similar to 2015 ESAC-Net data (11·7 to 38·3 DID; mean 22.6 DID). DDD changes in 2019 impact both total and relative consumption estimates: total DIDs reduced on average by 12·0% (7·3-35·5 DID), mostly due to reduced total DDDs for commonly used penicillins; impact on rankings and relative use estimates were modest. Discussion Quantitative metrics of antibiotic consumption have value. Improvements over time reflect national activities, however, changes in total volumes may conceal shifts to less desirable choices. Relative use measures targeting antibiotics of concern may be more informative. Some, including WHO Watch and Reserve classifications, lend themselves to prescribing targets supported by guidelines and treatment protocols.